2003
DOI: 10.1016/s0041-1345(03)00364-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycophenolate mofetil regimen on peripheral blood lymphocyte subsets in kidney transplant recipients

Abstract: Background and Aims. There is growing evidence of the effects of immunosuppressive agents on "immune targets" in renal transplantation. Immunological monitoring could indirectly measure the suppressive effect of these drugs and guide early preventive interventions in transplant recipients. Due to the selective antiproliferative effect of mycophenolate mofetil (MMF) on lymphocytes, our goal was to determine whether MMF modulates peripheral blood lymphocyte subsets (PBLS) in kidney allograft patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This may be due to the selective responses of immunosuppressive agents when administered as different combined therapy regimens with respect to the disease. In this regard, studies of BravoSoto et al, 16 have shown that CD19+ cells are reduces in renal allograft patients after treatment with azathioprine, prednisone and cyclosporine A 16. However in those studies CD3(+), CD3(+)CD4(+), CD3(+)CD8(+), were also reduced in kidney transplant patients 16, whereas in our studies these cells either increased (CD3+CD4+) or remained the same (CD3(+)CD8(+)).…”
Section: Discussionmentioning
confidence: 96%
“…This may be due to the selective responses of immunosuppressive agents when administered as different combined therapy regimens with respect to the disease. In this regard, studies of BravoSoto et al, 16 have shown that CD19+ cells are reduces in renal allograft patients after treatment with azathioprine, prednisone and cyclosporine A 16. However in those studies CD3(+), CD3(+)CD4(+), CD3(+)CD8(+), were also reduced in kidney transplant patients 16, whereas in our studies these cells either increased (CD3+CD4+) or remained the same (CD3(+)CD8(+)).…”
Section: Discussionmentioning
confidence: 96%
“…Decreasing lymphocyte proliferation is a crucial effect of MMF administration and is concentration‐dependent . Regulating an inappropriate immune response by inhibition of T cells is important because T cells contribute to autoimmune diseases by multiple stimulatory, activation, and cytotoxic mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest that a dosage ≥15 mg/kg would not be well tolerated by cats. Additionally, MMF may not have been given for a long enough time period, particularly considering that MPA has a cytostatic effect . Recent studies performed in healthy dogs suggest that MMF may need to be given for at least 2 weeks before decreased lymphocyte proliferation is observed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual effects of immunosuppressant drugs in organ transplant patients in general and in kidney transplant patients in particular need to be strictly controlled. Currently, the quantitative determination of calcineurin inhibitors has been carried regularly and mycophenolic acid (MPA) has been conducted at major transplant centers around the world to make a correlation between pharmacokinetics and clinical dosage (1). Although the biopsy provides a definitive diagnosis (2), the less interventional method offers an early diagnosis of transplant rejection, which is more beneficial for patients with kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%